Ginkgo biloba Extract Modulates the Retroperitoneal Fat Depot Proteome and Reduces Oxidative Stress in Diet-Induced Obese Rats - Hirata, Bruna K.S.; Pedroso, Amanda P.; Machado, Meira M.F.; Neto, Nelson I.P.; Perestrelo, Bruna O.; de Sá, Roberta D.C.C.; Alonso-Vale, Maria Isabel C.; Nogueira, Fernando N.; Oyama, Lila M.; Ribeiro, Eliane B.; Tashima, Alexandre K.; Telles, Monica M. (Frontiers in Pharmacology, 2019)
The rapid increase in the number of individuals with obesity, over the past four decades, is triggered by a number of complex interactions among factors. Despite the plethora of treatments available, side-effects are commonly observed and, in this context, herbal medicines have been employed as an alternative form of therapy. Ginkgo biloba extract (GbE) has been described as a promising new pharmacological approach to treat obesity. In order to better comprehend the mechanisms involved with this potential effect, the present study evaluated the effects of GbE treatment on diet-induced obese rats, focusing on the proteome and the oxidative stress defense system of visceral adipose tissue. After 14 days treatment, GbE significantly modulated 25 proteins. Retroperitoneal adipose tissue of treated animals exhibited higher amounts of proteins associated with adipogenesis (decorin), carbon metabolism and mitochondrial function (citrate synthase), and a concomitant reduction in adipocyte hypertrophy. In parallel, GbE down-regulated proteins involved in oxidative stress (peroxiredoxin) and the inflammatory response (complement C3, mast cell protease 1 and Ig gamma-2B chain C region). Moreover, also related to oxidative stress defense, GbE stimulated catalase activity, reduced malondialdehyde levels (lipid peroxidation indicator), and increased lactoylgluthatione lyase levels. It was concluded that GbE acts as an antioxidant agent, and improved the proteome profile and oxidative stress response in the adipose tissue of diet-induced obese rats.